The Response of South Africa’s Policy Landscape to Global and Local Trends - The Case of a Rural-Based University - Pillay, Pravina; Pillay, Thayabaran (International Journal of Criminology and Sociology, 2022)
Globalisation is a highly contested term and has become a site for tension. Whilst globalisation in the context of Higher Education must be lauded for giving students and scholars access to work on a global platform, it has also reinforced inequalities that are already prevalent and has even created new ones. The negative impact of globalisation is evident most explicitly in developing countries such as South Africa and in smaller institutions of Higher Learning such as the University of Zululand. To compound the already precarious situation, one finds that in addition to accommodating elements of globalisation, institutions of Higher Learning have to also accommodate local trends such as the Africanisation of Education. Whilst globalisation has swept across the world and has impacted almost every sphere of life, the foci of this paper is on how policies in Higher Education, with special reference to the University of Zululand, have responded to global trends and local needs. This is a qualitative study. The methodology used is document analysis. This study interrogates the Language and Research policies of the University of Zululand to illuminate on how the aforementioned institution responds to global and local needs. The main finding of the study is that institutions of Higher Learning, in crafting their policy documents, are incorporating globalisation and are finding innovative ways of embracing local trends at the same time.